Victims and memory after terrorism - Milošević, Ana (Victims, culture and society, 2024)
This book contributes to the study of collective memory and the sociology of terrorism by analysing the role of memorialization in relation to terrorism, its victims, and the broader society. While various social scientists have extensively theorized and analysed how trauma and memory interact, grow apart, and reinforce each other, this book puts the rights and needs of the victims centre-stage.